Discussion: Are the Origins of Indo-European Languages Explained by the Migration of the Yamnaya Culture to the West?. (28th July 2017) - Klejn, Leo S.; Haak, Wolfgang; Lazaridis, Iosif; Patterson, Nick; Reich, David; Kristiansen, Kristian; Sjögren, Karl-Göran; Allentoft, Morten; Sikora, Martin; Willerslev, Eske
Abstract : Two co-authored articles in Nature (Haak et al., 2015; Allentoft et al., 2015) caused a sensation. They revealed genetically the mass migration of steppe Yamnaya culture people in the Early Bronze Age to central and northern Europe. The authors considered this event as the basis of the spread of Indo-European languages. In response, the Russian archaeologist, Leo S. Klejn, expresses critical remarks on the genetic inference, and in particular its implications for the problem of the origins of Indo-European languages. These remarks were shown to the authors and they present their objections. Klejn, however, has come to the conclusion that the authors' objections do not assuage his doubts. He analyses these objections in a further response. Abstract : Deux articles parus dans la revue Nature (Haak et al., 2015 ; Allentoft et al., 2015) firent sensation. Ils révélaient, du point de vue génétique, qu'une migration de masse de peuples des steppes appartenant à la culture Yamna affecta l'Europe du centre et du nord à l'âge du Bronze Ancien. Leurs auteurs tiennent cet évènement comme formant la base de la diffusion des langues indo-européennes. En réponse, Prof. L.S. Klejn, archéologue à Saint Pétersbourg (Russie), émit certaines critiques à l'égard des déductions basées sur la génétique, en particulier ses répercussions sur la question des origines des langues indo-européennes. Ses remarques furent soumises aux auteurs des deux articles, qui à leur tour présentèrent leurs contre-arguments. Cependant Klejn en vint à conclure que les objections de ces auteurs n'ont pas atténué ses doutes, ce qui l'amène à une seconde réponse. Translation by Madeleine Hummler Abstract : Zwei Artikel, welche die Zeitschrift Nature in 2015 veröffentlichte (Haak et al., 2015; Allentoft et al., 2015), haben großes Aufsehen erregt. Diese lassen, aus genetischer Sicht, eine Massenmigration der Steppenvölker der Jamnaja-Kultur nach Mittel- und Nordeuropa in der Bronzezeit erkennen. Nach Auffassung der Verfasser bildet dieses Ereignis die Grundlage der Verbreitung der indoeuropäischen Sprachen. Als Antwort darauf äußerte sich Prof. L.S. Klejn (Archäologe in Sankt Petersburg, Russland) kritisch über die genetischen Rückschlüsse, besonders über die Auswirkungen auf die Frage des Ursprungs der indoeuropäischen Sprachen. Diese kritischen Bemerkungen wurden den Verfassern der Artikel vorgelegt und die Letzteren haben dann ihre Einwände dargelegt. Klejn ist aber zum Schluss gekommen, dass die Einwände der Verfasser ihn nicht überzeugen, und untersucht diese Gegenargumente in einer zweiten Antwort. Translation by Madeleine Hummler